Budget System Reform in Transitional Economies : The Experience of Russia - Diamond, Jack (IMF Working Papers; Working Paper, 2002)
This paper stresses the role of budget system reform in economies in transition as an essential basis for the implementation of effective fiscal policies. However, introducing such structural reforms in often unstable economic environments has not proved easy. Using Russia as a case study, the magnitude of the problems faced is documented, and the strategy of reform eventually adopted is critically reviewed. In conclusion, some lessons are drawn for other transitional countries undertaking similar reforms, and the future agenda for completing these reforms in Russia is indicated.